Color alteration of the paint used for iris painting in ocular prostheses - Aline Úrsula Rocha Fernandes; Marcelo Coelho Goiato; Marcos Antônio Jacó Batista; Daniela Micheline dos Santos (Sociedade Brasileira de Pesquisa Odontológica, 2009)
The purpose of this study was to assess color alteration of the paints used for iris painting in artificial eyes. Five disks of heat cured acrylic resin were confectioned by microwave energy for each paint analyzed, in a total of 40 specimens. Each specimen consisted of a colorless acrylic resin disk and another of equal size, of scleral white colored acrylic resin, with the painting interposed between the two disks. The specimens were submitted to an accelerated aging process in a chamber under ultraviolet radiation for 1,008 hours. To assess color variation, a reflective spectrophotometer was used. The results were statistically analyzed by ANOVA and the Tukey test (p < 0.05). All the paints underwent chromatic alteration. The oil paint presented the highest resistance to accelerated aging.